A QUANTITATIVE ASSESSMENT OF PERCEIVED ORGANISATIONAL SUPPORT AND WORK–LIFE BALANCE AS DETERMINANTS OF EMPLOYEE WELL-BEING IN THE INDIAN SERVICE SECTOR - Verma, Shivani; Garg, Pratibha; Anuradha, M V (ShodhKosh: Journal of Visual and Performing Arts, 2026)
This study examines the impact of Perceived Organizational Support (POS) and Work-Life Balance (WLB) on Employee Well-Being (EWB) in the Indian service sector. The study employeed a quantitative and descriptive design using stratified random selection of 172 employees, comprising 102 male and 70 females, was done based on their diverse job positions, level of education, employment, and industries. Instrumentation comprised validated tools, including the Survey of Perceived Organizational Support (SPOS), Hayman’s Work‑Life Balance Inventory, and the Workplace PERMA Profiler for employee well‑being. Structural equation modeling reveals significant positive relationships: WLB strongly predicts EWB (β=0.563, p<0.001), POS directly enhances EWB (β=0.361, p<0.001), and POS powerfully influences WLB (β=0.801, p<0.001). These findings highlight the importance of creating organizational environments that promote the work-life balance requirements of employees and, in the process, positively contribute to their general well-being and organizational commitment in the job market.The practical implications of the study indicate that the organizations in the service industry are advised to use supportive policies and flexible working schedules and facilitate leadership in which a culture of coperation and balance is cultivated. The future of the study will involve longitudinal research to determine the dynamics of Perceived Organizational Support (POS) and Work–Life Balance (WLB) across time and intervention unique to the sector to maximize the psychological health and productivity of the employee. The results offer practical insights to human resource managers who would want to improve employee retention and satisfaction by using supportive and flexible organizational policies. Overall, this paper has highlighted the importance of favorable organizational climates in enhancing sustainable employee welfare and performance in the changing service industry in India.